The power of certified common bean seeds - Lengewa, Catherine; Mikhala, Audrine; Aura, S; Amuda, Alex; Yila, Jummai; Bomuhangi, Allan; Nchanji, Eileen (2024)
Certified seeds guarantee purity, ensuring healthier plants and uniform growth. Farmers can see an increase in yield boost when using certified seeds, leading to better harvests. Certified bean seeds are bred to resist common diseases and pests, reducing the need for costly chemical treatments. These seeds are carefully selected for your region’s climate, ensuring better performance in wet and dry seasons. Buyers often prefer Beans from certified seeds, giving farmers a competitive edge in the market